SOME ASPECTS OF ECONOMIC DEVELOPMENT OF UKRAINIAN RAIL TRANSPORT - Drebot, Kh. V.; Snachov, M. P. (Science and Transport Progress, 2009)
The reserves of increasing the rail transport functioning efficiency in Ukraine in conditions of hard competition with other kinds of transport are considered.